2010
DOI: 10.1123/jsep.32.4.417
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Body-Related Self-Conscious Emotions in Motivating Women’s Physical Activity

Abstract: The purpose of this study was to test a model where body-related self-conscious emotions of shame, guilt, and pride were associated with physical activity regulations and behavior. Adult women (N = 389; M age = 29.82, SD = 15.20 years) completed a questionnaire assessing body-related pride, shame, and guilt, motivational regulations, and leisure-time physical activity. The hypothesized measurement and structural models were deemed adequate, as was a revised model examining shame-free guilt and guilt-free shame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
96
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 75 publications
9
96
1
8
Order By: Relevance
“…Recent investigations have extended this theory to the important health behavior of physical activity. Sabiston et al (2010) explored the relationship of body-related self-conscious emotions (shame, guilt, and authentic pride) with motivation regulations and behavior for physical activity in a large sample of adult females (18-68 years of age). The authors reported that body-related shame was positively related to maladaptive forms of motivation, negatively related to adaptive forms of motivation, and unrelated to physical activity behavior.…”
Section: Self-conscious Emotionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent investigations have extended this theory to the important health behavior of physical activity. Sabiston et al (2010) explored the relationship of body-related self-conscious emotions (shame, guilt, and authentic pride) with motivation regulations and behavior for physical activity in a large sample of adult females (18-68 years of age). The authors reported that body-related shame was positively related to maladaptive forms of motivation, negatively related to adaptive forms of motivation, and unrelated to physical activity behavior.…”
Section: Self-conscious Emotionsmentioning
confidence: 99%
“…Specifically, this set of emotions serves to motivate people to behave in moral and socially responsible ways (Leith & Baumeister, 1998) as well as foster perseverance in task and achievement domains (Stipek, 1995). Shame, guilt, and pride are the primary emotions studied within the context of self-conscious emotions and body image theories (Fredrickson & Roberts, 1997;Tracy & Robins, 2004), and are likely to be associated with health relevant processes such as physical activity behavior (Castonguay, Gilchrist, Mack, & Sabiston, 2013;Sabiston et al, 2010).…”
Section: Self-conscious Emotionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the few studies focusing on the analysis emotions within the fitness context, Collishaw, Dyer and Boies (2008) examined the effects of instructors' facial expressions on consumers' satisfaction with the staff performance. Sabiston et al (2010) studied how emotions such as body-related pride, shame and guilt, as well as motivational regulations and leisure-time physical activity are linked with women participation in fitness activities. These studies were important for the continued understanding of the role of emotions during fitness activities.…”
Section: Introductionmentioning
confidence: 99%